Modeling approach and numerical analysis of a roller-hearth reheating furnace with radiant tubes and heating process optimization - Qiang Gao (Elsevier, 2021)
Precise knowledge of the heat transfer in a reheating furnace is important for optimizing the slab production process. In the present work, a new comprehensive CFD (Computational Fluid Dynamics) model for simulating the gas flow, combustion and heat transfer in a roller-hearth reheating furnace with radiant tubes was developed. In the model, the slab dynamic heating process was performed based on the steady-state gas phase combustion in the furnace. The movement of slabs in the furnace was achieved by dynamic mesh. The radiant tubes and the furnace were coupled into a whole and the indirect heat transfer in the furnace was achieved by radiant tubes. The slab temperature predicted by the model showed a good agreement with the experimental results through the validation of “Black Box”. According to the simulation results, the temperature field in the furnace and the slab heating process were reasonably evaluated. Compared with the heating process with the slab residence time of 60min in actual production, the new heating process was determined by the simulating time for the whole slab reaching the austenitizing temperature and the holding time, and the slab residence time is 67min.